2006
DOI: 10.1016/j.ymgme.2006.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Propionyl-CoA and adenosylcobalamin metabolism in Caenorhabditis elegans: Evidence for a role of methylmalonyl-CoA epimerase in intermediary metabolism

Abstract: We have utilized Caenorhabditis elegans to study human methylmalonic acidemia. Using bioinformatics, a full complement of mammalian homologues for the conversion of propionyl-CoA to succinyl-CoA in the genome of C. elegans, including propionyl-CoA carboxylase subunits A and B (pcca-1, pccb-1), methylmalonic acidemia cobalamin A complementation group (mmaa-1), co(I) balamin adenosyltransferase (mmab-1), MMACHC (cblc-1), methylmalonyl-CoA epimerase (mce-1) and methylmalonyl-CoA mutase (mmcm-1) were identified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…Mut and wild-type murine embryonic fibroblasts have been described[24,25] and were isolated after a timed mating between mice carrying a targeted deletion of the Mut gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mut and wild-type murine embryonic fibroblasts have been described[24,25] and were isolated after a timed mating between mice carrying a targeted deletion of the Mut gene.…”
Section: Methodsmentioning
confidence: 99%
“…A murine methylmalonyl-CoA mutase cDNA that contained a consensus Kozak sequence and minimal untranslated regions was isolated from C57/BL6 liver RNA after RT-PCR, sequenced and tested for enzymatic activity after expression in yeast using the succinate-thiokinase linked assay[25]. The gene was then cloned as an EcoRI fragment into the polylinker of pShuttle between the CMV promoter and the Sv40 polyadenylation signal (ViraQuest Inc., North Liberty, IA).…”
Section: Methodsmentioning
confidence: 99%
“…MMCE catalyzes the conversion of (2R)-methylmalonyl-CoA to (2S)-methylmalonyl-CoA, the substrate for the B 12 -dependent methylmalonyl-CoA mutase. MMCE is widely found and essential in the breakdown of odd-chain fatty acids and branched amino acids [33][34][35]. The Propionibacteriumshermanii enzyme is activated to the greatest extent by Co 2+ , but also by Ni 2+ , Mn 2+ , and Zn 2+ , and the rat liver enzyme by Fe 2+ , Mn 2+ , and Co 2+ [36,37].…”
Section: Isomerase Family: Glyoxalase I Methylmalonyl-coa Epimerasementioning
confidence: 99%
“…In addition, we selected three genes known to encode propionyl Coenzyme A (PCCB), methylmalonyl CoA epimerase (MCEE), and methylmalonyl CoA mutase (MUT) respectively, which are involved in the essential process of conversion of propionyl-CoA to succinylCoA. A lesion at the epimerase step of methylmalonyl-CoA metabolism can cause malfunction of MCEE, which may cause methylmalonicacidemia in humans [6]. The last two candidate genes chosen in the propanoate metabolic pathway were ACSS1 and ACSS2, which are known to be highly expressed in the livers of mice to produce lipogenic enzymes that incorporate acetate into lipids [15,16].…”
Section: Selection Of Candidate Genes and Snpsmentioning
confidence: 99%
“…The regulatory mechanisms of the propanoate and fatty acid metabolic pathways have not been clarified. Reports have indicated that genes within the two essential pathways are directly involved with anabolism and catabolism, and they can therefore be speculated to have an effect on the growth of an organism [6][7][8].…”
mentioning
confidence: 99%